The Effect of Financial Distress, Company Size, and Audit Quality on the Going Concern Opinion - Santy Setiawan; Rapina .; Yenni Carolina; Kevan Hidayat (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2021)
Since 2020, the Covid-19 pandemic has affected the Indonesian economy and the company's going concern. Therefore, the purpose of this study is to examine the factors that influence an auditor to issue a going concern opinion about a company, particularly the effect of financial distress, company size, and audit quality. Data was collected from property companies listed on the Indonesia Stock Exchange for three years, from 2018 to 2020, using financial statement data. Furthermore, logistic regression was used as the test tool to determine the effect of the independent variable on the dependent. The results showed that financial distress affects going concern opinion, while company size and audit quality do not.Keywords: Keywords: financial, quality, and going concern